1994
DOI: 10.1021/ja00082a025
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics in Polydimethylsiloxane: The Effect of Solute Polarity

Abstract: The temperature dependent dynamics of polydimethylsiloxane (PDMS) melts are investigated by measuring orientational relaxation of a dissolved probe molecule, 2-naphthyltriethoxysilane (NTES) using time resolved fluorescence depolarization. The temperature dependent viscosity of PDMS is also reported for two molecular weights. The measurements of nonpolar NTES probe dynamics are compared to previous measurements on the polar probe, N-(triethoxysilylpropy1)dansylamide. The activation energies for the orientation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(43 citation statements)
references
References 0 publications
0
43
0
Order By: Relevance
“…We note that in studies of solute orientational relaxation in PDMS melts, [46] strong intermolecular interaction between a polar solute and the PDMS backbone resulted in significantly larger activation energies for solute reorientation when compared with a nonpolar solute. In addition, the intermolecular interaction was also postulated to perturb the physical properties of PDMS by impeding rotation about the Si-O bond.…”
mentioning
confidence: 85%
“…We note that in studies of solute orientational relaxation in PDMS melts, [46] strong intermolecular interaction between a polar solute and the PDMS backbone resulted in significantly larger activation energies for solute reorientation when compared with a nonpolar solute. In addition, the intermolecular interaction was also postulated to perturb the physical properties of PDMS by impeding rotation about the Si-O bond.…”
mentioning
confidence: 85%
“…Although the relationship between d and swelling is not linear and differs for each solvent system, it is expected that a solvent with d similar to that of PDMS will swell PDMS. [45][46][47][48] This is not surprising considering that solubility is measured by the degree of swelling of materials such as cross-linked polymers that do not dissolve. [43][44][45][46] It was also found that a solvent with high swelling of PDMS showed high solubility.…”
Section: Resultsmentioning
confidence: 99%
“…[45][46][47][48] This is not surprising considering that solubility is measured by the degree of swelling of materials such as cross-linked polymers that do not dissolve. [43][44][45][46] It was also found that a solvent with high swelling of PDMS showed high solubility. 29 PDMS has a low dipole moment, i.e., low polar properties, 45 so nonpolar solvents such as benzene, pentane, cyclic hydrocarbons, aromatic hydrocarbons, halogenated compounds, and ethers (diethyl ether, dimethoxyethane, tetrahydrofuran) revealed high solubility and high swelling.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, the experimental approach is the measurement of electronic excitation transport (EET) by observation of time-resolved fluorescence polarization anisotropy, r(t), among naphthalene chromophores attached in low concentration to what are essentially polystyrene chains. This method has been applied to the study of polymer glasses, [1][2][3][4][5] melts, [6][7][8] and blends. 4,8,9 To investigate polymer structure with EET-induced fluorescence depolarization, it is necessary to incorporate fluorophores into the polymer chains.…”
Section: Introductionmentioning
confidence: 99%